ENEGRY EFFICENT 3Ф SQUIRREL CAGE INDUCTION MOTOR AND ITS DYNAMIC MODELLING - Suresh D, Vibin R, Deepakraja C, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Three phase induction motors are employed in almost all the industries for its simple construction and easy operation. It is predicted that more than 60% of the electrical energy generated is being consumed by the induction motors. Any attempt to improve the efficiency and power factor will be cost effective. A multi Winding Induction Motor (MWIM) would be an alternative for the induction motor which efficient operation with power factor improvement is possible. MWIM consists of more than three windings on the same stator Core and conventional squirrel cage rotor. One set of windings is connected to a three phase supply which works as a conventional induction motor to meet the mechanical load. In addition, energy conservation is possible due to loading the multi set of winding for which separate supply is not required.